EKOSISTEM KORPORASI PETANI JAGUNG DI KABUPATEN BANDUNG - Puspita, Gusti Reza; Karyani, Tuti; Setiawan, Iwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Farmer corporations are farmer economic institutions with legal entities in the form of cooperatives, as well as farmer-owned enterprises (BUMP) in the form of limited liability company (PT) or trading enterprises (UD), with most of the capital ownership owned by farmers so that they have a bargaining position over the products produced. The business model that the corporation wants to build includes the entire process of processing crops, from packaging to branding to marketing strategy, including connecting all of this with the banking system, technology innovators, and management that is able to manage everything well. Therefore, several stakeholders are needed, including the government, farmers, banking, universities, off-takers, insurance, agro-inputs, and technology. This study aims to see how the implementation of the Penta helix collaboration model increases the potential for cooperative competitiveness among corn farmers in Bandung Regency. This study used an in-depth interview method with informants, namely the management of the Sinar Corn Priangan Producers Cooperative, representatives of the Agricultural Extension Sector of the Bandung Regency Agricultural Service, and BNI Bank employees in the People's Business Credit (KUR) section. The results of this study indicate that all the pillars or parts of the Penta helix have been realized and implemented in the Bandung Regency Corn Farmers Corporation. The role of each pillar is in accordance with the opportunities and developments from time to time. The synergistic cooperation of all Penta helix elements involved in the development of the Bandung Regency Corn KORPORASI PETANI has resulted in the awarding of several awards for their achievements.